2019
DOI: 10.33828/sei.v30.i4.14
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Epistemological Beliefs and the Influence of Professional Development

Abstract: This study explored the epistemological beliefs of the science faculty at a small liberal arts college in the Southern United States and investigated the effect of a Faculty Learning Community (FLC) professional development (PD). The teacher beliefs interviews (Luft and Roehrig, 2007) were used to investigate epistemological beliefs of faculty from various science, technology, engineering, and mathematics (STEM) disciplines for three semesters. The faculty members were grouped into two categories: Those who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Letina (2022) found that it is crucial for educators to regularly assess their teaching practices and they should reflect on their beliefs about teaching and learning in order to identify areas for improvement and teachers can refine their epistemic beliefs by engaging in discussions and conversations with colleagues, mentors, and other educators. Epistemic beliefs can also be developed by staying informed about the latest developments in education (Mataka et al, 2019). Implementing student-centered learning strategies in the classroom can help educators better understand including their beliefs about teaching and learning, as well as the learning strategies used by their students (Lammassaari et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Letina (2022) found that it is crucial for educators to regularly assess their teaching practices and they should reflect on their beliefs about teaching and learning in order to identify areas for improvement and teachers can refine their epistemic beliefs by engaging in discussions and conversations with colleagues, mentors, and other educators. Epistemic beliefs can also be developed by staying informed about the latest developments in education (Mataka et al, 2019). Implementing student-centered learning strategies in the classroom can help educators better understand including their beliefs about teaching and learning, as well as the learning strategies used by their students (Lammassaari et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the design of activities and materials, current research indicates that the role of pedagogical practices and learning experiences presents challenges for both faculty and students in terms of necessary materials (Tadesse et al, 2020). Furthermore, faculty members are always willing to introduce changes in teaching methodology (Mataka et al, 2022). These changes or planned strategies are aimed at achieving academic goals, with the condition of achieving academic success through learning (Ayu, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, STEM-based differentiated learning is one of the effective learning models in encouraging students' critical thinking skills. STEM is a learning approach that combines Science Technology Engineering and Methematic in the learning process (Rahming, 2022;Putra et al, 2023;Zulyusri et al , 2023;Mataka et al, 2020;Aldahmash et al, 2019). STEM learning is able to encourage students to be more creative and innovative in learning (López-belmonte & González, 2022;Baran et al, 2021;Siew & Ahmad, 2023;Sevimli & Ünal, 2022).…”
Section: Introductionmentioning
confidence: 99%